Kabale University Policy on Promoting Staff Academic Growth and Professional Development - Kabale University (Kabale University, 2022)
This policy applies to Kabale University staff members employed on a full-time basis. The University recognizes that staff growth and development is a continuous process. The success of such a process depends on a set of systematic guidelines and procedures to be followed in assisting staff members to achieve their fullest potentials as academics and administrators. The University recognizes the need to develop a policy to promote the growth and development of its members of staff within the framework of these guiding factors. The training guidelines and procedures outlined here constitute the University’s policy on promoting the academic/administrative growth and professional development of its members of staff